Lateral shear interferometry for shape accuracy measurements of 3D-printed micro-optics - Zhao Yanqiu; Wang Lunwei; Siegle Leander; Giessen Harald (Current Directions in Biomedical Engineering)
The technique of 3D-printed micro-optics has experienced significant advancements over the last few years [1, 2]. This progressive evolution has been marked by remarkable strides in precision and miniaturization, making it particularly attractive to applications in the field of medical endoscopy. One noteworthy application entails the fabrication of micro-lenses directly on optical fibers, thereby creating endoscopic devices with unparalleled capabilities. A significant attribute of these micro-optical systems lies in their capability for precise imaging and their adept navigation through exceptionally narrow biological structures. For instance, the application of the 3D-printed endoscopy technology has facilitated insertion into the aorta of mice, as well as severely diseased human carotid arteries [2, 3]. This unprecedented level of accessibility and adaptability holds immense promise for diagnostic and therapeutic interventions in the realm of cardiovascular medicine and beyond. In the future, it may also be conceivable for micro-lenses to serve not only as imaging tools, but also as integral components of 3D-printing processes aimed at repairing damaged human tissue with bio-materials. For micro-lens production and quality control, performance assessment is invariably necessary to assure diffraction limited imaging in the different optical applications. With confocal surface profiling, only the surface shape information of micro-optics can be obtained. However, not only the shape of 3D-printed optics is relevant for its quality, but also its refractive index distribution is crucial when determining its overall optical performance. Therefore, the measurement of the wavefront is decisive in evaluating lens performance. Lateral shear interferometry presents itself as a compact and precise method for wavefront measurements. The only essential component required in the set-up is a pair of glass plates with high surface quality. Consequently, the entire set-up can be notably streamlined, as there is no requirement to construct an interferometer reference arm. This advantage facilitates the development of a notably compact set-up, making lateral shear interferometry particularly advantageous for integration with microscope and 3D-printer, despite the requirement for more complex algorithms in analyzing lateral shear interferograms. In this paper, simulation of shear interferogram fringes corresponding to wavefronts exhibiting varying aberrations are discussed. Additionally, this research encompasses measurement and analysis of shear interferograms obtained from wave fronts transmitted through different lenses. Through meticulous examination of these experimental results, the characteristics and performance of the tested optical systems are elucidated, contributing to a deeper understanding of wavefront analysis methodologies and their applicability in optical characterization studies.